Clinical Anatomy of Submental Intubation: A Review of the Indications, Technique, and a Modified Approach. Issue 2 (February 2020) - Jacob, DeAsia D.; Tuncer, Fatma B.; Kashan, David L.; Gurunluoglu, Raffi
Abstract : Abstract: Since its original description in 1986 by Hernandez, submental intubation has been used in a wide variety of craniomaxillofacial cases as a way to satisfy both surgeon and anesthesiologist to provide access to necessary surgical sites and airway protection. Many modifications to the original technique have been described. There has been a paucity of plastic surgery literature over the last 10 years that have reviewed the anatomy, technique, and complications. In this article, the authors review the pertinent anatomy related to this method of intubation. A cadaver was used to enhance visualization of important structures and to show the modification used by our group. Submental intubation provides a useful alternative to tracheostomy in several craniomaxillofacial procedures. Our approach uses a reinforced endotracheal tube to prevent kinking and provide additional intraoperative protection of the airway. Submental intubation may be indicated in select patients undergoing craniomaxillofacial surgery. Therefore, it is pertinent to be aware of the important anatomy and the complications of this technique to appropriately counsel patients. Our modification provides safe airway control.